Metode Forward Chaining Dan Certainty Factor Untuk Antisipasi Kecanduan Game Online Berbasis Web - Abid Nur Rahman; Eka Januar Karim (Riset Sinergi Indonesia (RISINDO), 2022)
Games are everyone's favorite. Both children and adults enjoy playing games. A person can continuously play games to the point of forgetting time and even forgetting the environmental conditions around him. The frequency of playing games can have an impact on a person's level of addiction to games. However, not everyone is aware that they have this type of gaming addiction. Therefore, a study was conducted to identify the types of game addiction behavior. Expert systems are usually used for consultation, analysis, diagnosis and help make decisions. So we need a system that can help solve this problem in the form of an expert system using the certainty factor (CF) method. This application is made using the Forward Chaining and Certainty Factor methods with the PHP and MySQL programming languages as the database. This research will produce an expert system application for diagnosing online game addiction with the output of the probable disease along with the percentage. It is hoped that by applying the forward chaining method and the certainty factor to online game addiction, so that decisions can be made precisely and accurately